Clinical study of ganshuang granule combined with tenofovir in the treatment of chronic hepatitis B complicated with nonalcoholic fatty liver disease - Su, Changtian; Yang, Qin (Frontiers in Pharmacology, 2022)
Objective: This study aims to investigate the clinical efficacy of Ganshuang granules combined with tenofovir, an antiviral drug, in the treatment of chronic hepatitis B complicated with nonalcoholic fatty liver disease. Methods: A total of 92 patients with chronic hepatitis B combined with non-alcoholic fatty liver who were treated in our Hospital from January 2020 to December 2021 were included as the research objects. According to the method of random number table, the patients were divided into the control group (n = 42) and the treatment group (n = 50). The control group was treated with silibinin meglumine tablets and tenofovir, while the treatment group was treated with Ganshuang granules combined with silybin meglumine tablets and tenofovir. Before and after treatment, liver function index, liver hardness measurement (LSM), controlled attenuation parameter (CAP), HBV-DNA serum load and body mass index (BMI) were observed. Results: Compared with the baseline, ALT, AST and GGT were significantly improved in both groups after treatment (p < 0.05), while TBIL indexes were not significantly different before and after treatment (p > 0.05). Patients in the treatment group had significantly lower ALT and AST index values than the control group at 12 and 24 weeks of treatment (p < 0.05). At 12 and 24 weeks of treatment, the fat attenuation parameters of the two groups were significantly decreased compared with those before treatment, and the difference was statistically significant (p < 0.05). The fat attenuation parameters in the treatment group were significantly lower than those in the control group at 12 and 24 weeks after treatment (p < 0.05). Conclusion: The effect of Ganshuang granule combined with antiviral drugs in the treatment of chronic hepatitis B complicated with non-alcoholic fatty liver is significantly better than that of antiviral drugs alone, which is worthy of clinical recommendation. Systematic Review Registration:https://register.clinicaltrials.gov, identifier NCT05523648.